Histone Demethylase KDM4A Inhibition Represses Neuroinflammation and Improves Functional Recovery in Ischemic Stroke - Liu, Yanfei; Zhao, Liang; Zhang, Jianzhong; Lv, Liquan; Han, Kaiwei; Huang, Chengguang; Xu, Zheng (Current Pharmaceutical Design, 2021)
Background: Epigenetic regulation concerning histone lysine methylation and demethylation play a crucial role in cerebral ischemic injury. Dysregulation of histone methylation modifiers has been identified in cerebral ischemia. However, the function and the underlying mechanisms of histone demethylase KDM4A on neuroinflammation and functional recovery in ischemic stroke remains unclear. Methods: In the present study, the rat model of transient middle cerebral artery occlusion (MCAO) was established, and the expression level of KDM4A was assessed in brain tissues. KDM4A inhibition was carried out by intrathecal injection with Lv-shKDM4A, and then pro-inflammatory cytokines and neurological functional tests were assessed. Results: We demonstrated that rats subjected to MCAO showed a markedly increased expression of KDM4A, pro-inflammatory cytokines IL-1β and TNF-α, and vascular endothelial growth factor (VEGF), whereas KDM4A inhibition repressed the expression of IL-1β, TNF-α and VEGF both in MCAO and oxygen-glucose deprivation (OGD) models. Furthermore, KDM4A inhibition showed a marked improvement in spatial learning and sensorimotor function, as suggested by mNSS and foot-fault test, respectively. Mechanistically, KDM4A inhibition repressed NF-ΚB signaling activation in microglia as indicated by decreased expression and nuclear translocation of p65 in vitro and in vivo. The effects of KDM4A overexpression on exacerbating neuroinflammation was inhibited by additional treatment of NF-ΚB inhibitor (JSH-23). Conclusion: The current results demonstrated KDM4A inhibition improves functional recovery in ischemic stroke by repressing NF-ΚB activation and subsequent neuroinflammation.
Keywords: TNF-α